login  home  contents  what's new  discussion  bug reports     help  links  subscribe  changes  refresh  edit

Edit detail for SandBoxFriCAS revision 9 of 50

1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50
Editor: test1
Time: 2013/03/15 06:55:45 GMT-7
Note:

changed:
-solve(s=vt+at^2/2,t)
solve(s=v*t+a*t^2/2,t)

changed:
-radicalsolve(s=vt+at^2/2,t)
radicalSolve(s=v*t+a*t^2/2,t)

changed:
-solve(vt+at^2/2-s=0,t)
solve(v*t+a*t^2/2-s=0,t)

removed:
-\begin{axiom}
-solve(vt+at/2-s=0,t)
-\end{axiom}
-
-From meliusja Tue Apr 8 10:42:11 -0700 2008
-From: meliusja
-Date: Tue, 08 Apr 2008 10:42:11 -0700
-Subject: 
-Message-ID: <20080408104211-0700@axiom-wiki.newsynthesis.org>
-

This page is set to execute \begin{axiom}... \end{axiom} commands using FriCAS?:

axiom
)version
Value = "FriCAS 2012-10-18 compiled at Thursday March 14, 2013 at 16:23:44 "

Any comments added here with use this version of FriCAS?.

axiom
solve(s=v*t+a*t^2/2,t)

\label{eq1}\left[{{{2 \  t \  v}+{a \ {{t}^{2}}}-{2 \  s}}= 0}\right](1)
Type: List(Equation(Fraction(Polynomial(Integer))))

axiom
radicalSolve(s=v*t+a*t^2/2,t)

\label{eq2}\left[{t ={{-{\sqrt{{4 \ {{v}^{2}}}+{8 \  a \  s}}}-{2 \  v}}\over{2 \  a}}}, \:{t ={{{\sqrt{{4 \ {{v}^{2}}}+{8 \  a \  s}}}-{2 \  v}}\over{2 \  a}}}\right](2)
Type: List(Equation(Expression(Integer)))

axiom
solve(v*t+a*t^2/2-s=0,t)

\label{eq3}\left[{{{2 \  t \  v}+{a \ {{t}^{2}}}-{2 \  s}}= 0}\right](3)
Type: List(Equation(Fraction(Polynomial(Integer))))

axiom
solve(v*t+a*t/2-s=0,t)

\label{eq4}\left[{t ={{2 \  s}\over{{2 \  v}+ a}}}\right](4)
Type: List(Equation(Fraction(Polynomial(Integer))))

axiom
solve(v*t+a*t^2/2-s=0,t)

\label{eq5}\left[{{{2 \  t \  v}+{a \ {{t}^{2}}}-{2 \  s}}= 0}\right](5)
Type: List(Equation(Fraction(Polynomial(Integer))))

axiom
radicalSolve(p^3 - p + 1/10=0,p)

\label{eq6}\begin{array}{@{}l}
\displaystyle
\left[{p ={{{{\left(-{3 \ {\sqrt{- 3}}}+ 3 \right)}\ {{\root{3}\of{{-{3 \ {\sqrt{3}}}+{\sqrt{-{373}}}}\over{{60}\ {\sqrt{3}}}}}^{2}}}- 2}\over{{\left({3 \ {\sqrt{- 3}}}+ 3 \right)}\ {\root{3}\of{{-{3 \ {\sqrt{3}}}+{\sqrt{-{373}}}}\over{{60}\ {\sqrt{3}}}}}}}}, \: \right.
\
\
\displaystyle
\left.{p ={{{{\left(-{3 \ {\sqrt{- 3}}}- 3 \right)}\ {{\root{3}\of{{-{3 \ {\sqrt{3}}}+{\sqrt{-{373}}}}\over{{60}\ {\sqrt{3}}}}}^{2}}}+ 2}\over{{\left({3 \ {\sqrt{- 3}}}- 3 \right)}\ {\root{3}\of{{-{3 \ {\sqrt{3}}}+{\sqrt{-{373}}}}\over{{60}\ {\sqrt{3}}}}}}}}, \: \right.
\
\
\displaystyle
\left.{p ={{{3 \ {{\root{3}\of{{-{3 \ {\sqrt{3}}}+{\sqrt{-{37
3}}}}\over{{60}\ {\sqrt{3}}}}}^{2}}}+ 1}\over{3 \ {\root{3}\of{{-{3 \ {\sqrt{3}}}+{\sqrt{-{373}}}}\over{{60}\ {\sqrt{3}}}}}}}}\right] (6)
Type: List(Equation(Expression(Integer)))

axiom
R1 ==> Record(foo1: String, remLexs: List Integer)
Type: Void
axiom
R2 ==> Record(foo2: String, remLexs: List Integer)
Type: Void
axiom
r1: R1 := ["a", [1,2,3]]

\label{eq7}\left[{foo 1 = \mbox{\tt "a"}}, \:{remLexs ={\left[ 1, \: 2, \: 3 \right]}}\right](7)
Type: Record(foo1: String,remLexs: List(Integer))
axiom
r2: R2 := ["b", [5]]

\label{eq8}\left[{foo 2 = \mbox{\tt "b"}}, \:{remLexs ={\left[ 5 \right]}}\right](8)
Type: Record(foo2: String,remLexs: List(Integer))
axiom
r1.remLexs

\label{eq9}\left[ 1, \: 2, \: 3 \right](9)
Type: List(Integer)
axiom
r2.remLexs

\label{eq10}\left[ 5 \right](10)
Type: List(Integer)